2010
DOI: 10.4049/jimmunol.1000893
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovani Promastigotes Evade the Antimicrobial Activity of Neutrophil Extracellular Traps

Abstract: Upon their recruitment to a site of infection and their subsequent activation, neutrophils release DNA and a subset of their granule content to form filamentous structures, known as neutrophil extracellular traps, which capture and kill microorganisms. In this study, we show that Leishmania promastigotes induced the rapid release of neutrophil extracellular traps from human neutrophils and were trapped by these structures. The use of Leishmania mutants defective in the biosynthesis of either lipophosphoglycan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
130
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(141 citation statements)
references
References 52 publications
6
130
2
3
Order By: Relevance
“…This finding was further corroborated by Gabriel and colleagues (13), who demonstrated that L. donovani also induces NET formation. In addition, upon interaction with neutrophils, promastigotes of Leishmania infantum activate NETosis in a time-and dose-dependent manner ( Fig.…”
Section: Leishmania Infantum Promastigotes Induce the Release Of Neutsupporting
confidence: 70%
See 4 more Smart Citations
“…This finding was further corroborated by Gabriel and colleagues (13), who demonstrated that L. donovani also induces NET formation. In addition, upon interaction with neutrophils, promastigotes of Leishmania infantum activate NETosis in a time-and dose-dependent manner ( Fig.…”
Section: Leishmania Infantum Promastigotes Induce the Release Of Neutsupporting
confidence: 70%
“…Promastigotes of Leishmania infantum induced NETosis in a dose-and time-dependent manner. Furthermore, NET induction seems to be conserved in different species of Leishmania (12,13). In addition, as previously reported, human neutrophil donors differed in the magnitude of their NET response to different stimuli (3).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations